Analysis of polychlorinated biphenyls in sewage sludge using supercritical carbon dioxide and subcritical water extraction - Ab. Halim, Ahmad Zamani (2007)
Extractions of polychlorinated biphenyls (PCBs) for sewage sludge are often time consuming and involved the use of large volume of organic solvents. In this study, a supercritical fluid carbon dioxide (SFCO2) extraction and subcritical water extraction (SWE) were developed with the aim of overcoming the disadvantages associated with the conventional Soxhlet extraction. The SFE conditions utilised extraction temperature of 60oC, extraction pressure of 200 bar, 15% methanol as cosolvent, extraction flow rate at 2.0 mL/min, 30 minute extraction and n-hexane as the analyte trapping solvent for PCBs extraction from sludge. A lab-made SWE extraction system was successfully developed for the dynamic SWE of PCBs from sludge samples. For the SWE, the optimized condition employed an extraction temperature of 250oC, extraction pressure of 50 bar, 1 min static followed by 10 min dynamic extraction and analyte collection in dichloromethane. Both the SFCO2 extraction and SWE showed good PCB recoveries (50 to 99%) compared to Soxhlet extraction (52 to 75% PCB recoveries). Comparison of PCBs extracted with Soxhlet extraction revealed that SFCO2 extraction and SWE to be fast, easy, and environmentally clean techniques. From the two extraction methods investigated, it was clear that the SFCO2 technique was better in terms of recovery, good reproducibility and speed of analysis compared to the SWE method and was therefore chosen as the method of choice for the analysis of real sludge samples. The PCBs under study (PCB 28, 52, 101, 118, 138, 153 and 180) when analysed using gas chromatography electron capture detector gave low detection limit in the range of 0.016 to 0.048 µg/mL. The concentration of PCBs in sludge samples extracted using SFCO2 were in the range of 31.2 to 82.0 µg/kg as compared to that using Soxhlet extraction with PCB levels from 20.2 to 60.1 µg/kg. The characterization of sludge samples from other aspects was also carried out. The sludge samples showed slightly acidic pH values ranging from 4.3 to 6.6. All samples were found to be chemically stable and the percentages of nutrient (nitrogen, phosphorus and potassium) were in the range of 0.059 to 0.98%, 0.05 to 0.15% and 0.12 to 0.16%, respectively. Heavy metal studies showed that metal content in municipal sewage sludge samples were below the United States Environmental Protection Agency limit.